Foreign Bodies in the Ear Canal in Children: A Literature Review - Barański, Marcin; Wasiniewska, Weronika; Kandefer, Tomasz; Sroka, Maria Izabela (Quality in Sport, 2026)
Foreign bodies in the external auditory canal (EAC) are a common pediatric emergency, especially in children aged 1–4 years due to exploratory behavior and limited risk awareness. Common objects include beads, toy parts, organic materials, and button batteries, the latter posing significant risk of tissue damage. Clinical presentation ranges from asymptomatic cases to otalgia, hearing loss, and otorrhea. Diagnosis relies primarily on history and otoscopic examination, with imaging reserved for selected cases. Management should be prompt and individualized, using techniques such as forceps, suction, hooks, or irrigation, while complex cases may require sedation or general anesthesia. Delayed or unsuccessful removal increases complication risk, including infection and tympanic membrane perforation. Early recognition, appropriate management, and caregiver education are essential to prevent complications and improve outcomes.